PROFIL MUKA AIR DI HULU GROUNDSILL TIPE AMBANG LEBAR DAN OGEE - Wahyu Widiyanto (Dinamika Rekayasa, 2007)
A Groundsill is built with main purpose to control river bed. When groundsill is placed in a river there will cause water surface raises and creates backwater in upstream of the groundsill. It influences elevation of flood and inundation. The backwater will inundate riverbank or structures along backwater distance, and drainage become difficultier as well as cause dangerous spill. Different type of groundsill will give different inundation impact. Therefore it needs to analyse water surface raises caused by different type of groundsill. This study is aimed to analyse water surface profile in upstream of groundsill with two different type, i.e. broadcrested and ogee. Serang River data is used to analyse. HEC-RAS Version 4 Beta assist the calculation and analysis. The calculation result shows that at the same height of sill, Ogee type give higher backwater level than broadcrested type. Nevertheless, the backwater distance is not different significantly.